Supply Chain Disruptions and Stock Prices: Chapter 6 - Conclusions - Schelp, Priscilla; Skipworth, Heather; Aktas, Emel; Vieth, Beate (Springer, 2024)
This chapter concludes the book, summarising key takeaways for both practitioners and academics on managing Hurricane-Related Risks based on our research findings. The summary encapsulates the critical outcomes of our research, shedding light on the intricate relationship between hurricanes, supply chain disruptions, and firm performance. Our study draws from a diverse range of academic sources, offering profound insights into the imperative of proactive management and transparent communication during hurricane-induced supply chain disruptions.
Keywords: 35 Commerce, Management, Tourism and Services; 3502 Banking, Finance and Investment; 3507 Strategy, Management and Organisational Behaviour; 3509 Transportation, Logistics and Supply Chains; 46 Information and Computing Sciences; 4609 Information Systems